PEMAHAMAN GURU MTs TERHADAP IMPLEMENTASI KEPUTUSAN DIRJEN PENDIS NOMOR 5162 TAHUN 2018 TENTANG PETUNJUK TEKNIS PENILAIAN HASIL BELAJAR PADA MADRASAH TSANAWIYAH - Haeruman (WIDYABORNEO, 2021)
Provisions regarding the assessment of learning outcomes in Madrasas are regulated through the Technical Guidelines, namely the Decree of the Director General of Islamic Education number 5162 in 2018 regarding the technical instructions for assessing learning outcomes in Madrasah Tsanawiyah. The 2013 curriculum assessment is expected to prioritize assessment as learning and assessment for learning compared to assessment of learning or learning outcomes. This means that the assessment is prioritizing to encourage or optimize the learning process, and assessment as part of the learning process, namely as a means of improving the learning process, not on learning outcomes. The value of completeness of knowledge and skills competencies is expressed in the form of numbers with a range of values ??0 (zero) - 100 (one hundred). In determining the substance of the material and the time needed to achieve mastery learning is determined solely by the teacher and education unit with reference to the development of student competencies and applicable regulations. Therefore, a teacher or educator must really understand the Technical Guidelines for the Decree of the Director General of Islamic Education number 5162 in 2018 regarding the technical instructions for assessing learning outcomes in Madrasah Tsanawiyah. So that in taking steps in teaching and learning activities in accordance with what is expected, both the educational unit and the Government's expectations. From the results of the study of this theory, it can be concluded that according to the Technical Guidelines, namely the Decree of the Director General of Islamic Education number 5162 in 2018 regarding the technical instructions for assessing learning outcomes in Madrasah Tsanawiyah, in its evaluation, it is more concerned with improving the learning process than learning outcomes.